2018
DOI: 10.1186/s12903-018-0521-7
|View full text |Cite
|
Sign up to set email alerts
|

What is the influence of tonsillectomy on the level of periodontal pathogens on the tongue dorsum and in periodontal pockets

Abstract: BackgroundFor periodontal treatment, the full mouth disinfection approach suggests disinfection of oral soft tissues, such as tongue and tonsils concomitant to scaling and root planning since patients might benefit from treatment of these oral niches either. Periodontopathogenes in tonsillar tissue support this hypothesis. This prospective controlled clinical study investigated the change in the oral flora of patients who underwent tonsillectomy. Pockets were tested for eleven bacterial species before and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Similarly, these anaerobic bacteria were found in tonsils with recurrent inflammation [25]. The present study was designed based on the anatomic nearness and bacterial similarity indicated in previous studies, suggesting the possibility of an association between the palatine tonsil area and periodontitis [18,22,[24][25][26].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Similarly, these anaerobic bacteria were found in tonsils with recurrent inflammation [25]. The present study was designed based on the anatomic nearness and bacterial similarity indicated in previous studies, suggesting the possibility of an association between the palatine tonsil area and periodontitis [18,22,[24][25][26].…”
Section: Introductionmentioning
confidence: 72%
“…A previous study reported that the microorganisms in the tongue area were altered following tonsillectomy [26]. The study showed that Tannerella forsythia and Porphyromonas gingivalis levels decreased in samples taken from the tongue after tonsillectomy [26]. This result could be explained by how anatomically close the tongue and tonsils are, and the fact that saliva is exchanged between them while speaking and swallowing.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Regarding the effect of tonsillectomy on infections in the oral cavity, for which periodontitis has been considered as a consequence of oral dysbiosis, parallel to the imbalance of anti‐microbial immunity and microbiota in the gastrointestinal tract, 9 a previous longitudinal cohort study reported that tonsillectomy had no effect on periodontal status and bacterial flora 32 over a 6‐week observational period in patients aged above 18 years. This agreed with part of our findings that the association between tonsillectomy and periodontitis was not significant in adults during a short‐period of follow‐up.…”
Section: Discussionmentioning
confidence: 99%